2007
DOI: 10.2337/db06-1027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Reconstitution of Autoimmune Type 1 Diabetes With Two Major Susceptibility Genes in the Rat

Abstract: The Komeda diabetes-prone (KDP) rat is an animal model of human autoimmune type 1 diabetes. We have previously shown that two major susceptibility genes, the major histocompatibility complex (MHC) RT1 u haplotype and Cblb (Casitas B-lineage lymphoma b) mutation, are responsible for the development of diabetes in KDP rats, suggesting a two-gene model for development of the disease. To confirm the two-gene model, we produced a congenic strain carrying mutated Cblb alleles of the KDP rat on a non-KDP genetic back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
(52 reference statements)
1
29
0
1
Order By: Relevance
“…The findings above extend previous evidence from the KDP rat strain that Cbl-b is important for regulating islet-specific autoimmunity (20)(21)(22) by showing that Cblb deficiency predisposes to diabetes and formation of islet autoantibodies in mice (Fig. 1).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The findings above extend previous evidence from the KDP rat strain that Cbl-b is important for regulating islet-specific autoimmunity (20)(21)(22) by showing that Cblb deficiency predisposes to diabetes and formation of islet autoantibodies in mice (Fig. 1).…”
Section: Discussionsupporting
confidence: 78%
“…The effects of Cblb deficiency are only manifest as autoimmunity when peripheral tolerance is stressed by increasing the frequency of autoreactive T cells through elevated thymic production in the TCR insHEL transgenic mice studied in this study. Similarly, the autoimmune effects of Cblb mutation in rats are only manifest as insulitis, diabetes, and thyroiditis when combined with a diabetessusceptible MHC haplotype (20)(21)(22) that, speculatively, may diminish thymic negative selection of islet-specific CD4 cells (47). Even with these combined defects, diabetes only develops after a variable latent phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that Cbl-b deficiency is associated with type II diabetes in mice. Yokoi et al [20,40] reported that loss of function due to mutated CBLB is associated with type I diabetes in rodents and humans. CBLB mutation causes autoimmune disease by impairing anergy induction in T-cells.…”
Section: Cbl-b In Aging-induced Macrophage Activationmentioning
confidence: 99%
“…Esta constatação evidencia a necessidade de levar ao conhecimento público os códigos éticos estabelecidos para a escolha do método a ser, ou já empregado, assim como a evolução dos resultados obtidos e que propiciaram avanços importantes para o conhecimento e tratamento, por exemplo, do Diabetes mellitus tipo 2 13 .…”
Section: Debates éTicosunclassified